KNOWING CATTLE ANIMALS AND THEIR BENEFITS AS LEARNING FOR EARLY CHILDREN - Yuli Arniati (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Early childhood is in the pre-operational stage, namely children aged 5-6 years. This stage is the initial period for children to build their ability to organize their thoughts. Early childhood begins to understand and recognize various kinds of objects and living things around them. For example, children are able to recognize the names of animals and their benefits for life, according to the themes studied in PAUD. Cows are one of the livestock that are widely used in everyday life, be it meat, milk, skin to bones and manure. The meat and bones can also be processed into various cuisines around the world. Cattle farming is very important in economic, environmental and cultural aspects. While it provides valuable products and livelihood opportunities, it also has a positive impact on people's lives. In PAUD children, an introduction to animals is also very important to convey in an interesting way. So, Early Childhood is able to recognize the environment that is around them.